The Influence Of Work Discipline And Giving Rewards On Employee Performance At PT. Mitra Yudhitama Medika Jakarta - Elyana, Instianti; Nelfianti, Fera; Suardhita, Nyoman; Karlina, Eulin (Jurnal Ekonomi, 2024)
This research adopts a quantitative descriptive approach using observation, questionnaires, documentation, and literature study methods. The population studied was 35 PT Mitra Yudhitama Medika Jakarta employees, using saturated sampling techniques. Data analysis uses a multiple linear regression model and SPSS version 26 software to calculate the results of the Multiple Linear Regression variable test, T-Test, and F Test and analyze the level of determination. The research results show that work discipline and giving rewards significantly influence the performance of PT Mitra Yudhitama Medika employees. High work discipline reflects adherence to rules and responsibilities, which increases productivity. Providing financial and non-financial rewards can motivate employees and increase their productivity. The third hypothesis test shows that work discipline and giving rewards jointly influence employee performance. This research emphasizes the importance of developing work discipline and reward systems in human resource management as a strategy to achieve company goals.